Investigation of a horizontal low power wind turbine - S. Yu. Shamanin; V. L. Blinov; V. V. Savchenko; Yu. M. Brodov (Известия высших учебных заведений: Проблемы энергетики)
THE PURPOSE. Development and creation of an experimental stand, carrying out a full-scale experiment, verification the numerical model of a NREL S809 airfoil based on its dimensionless characteristics, analyze the flow around the airfoil at different angles of attack.METHODS. A technique for studying the flow structure around a wind turbine using numerical methods of gas dynamics based on solving the system of Navier-Stokes equations is considered. Mathematical modeling methods were used using the k-ε and SST turbulence model.RESULTS. In this study, a laboratory stand is designed using CAD systems and created using additive FDM printing technologies An experimental study of the dependence of the rotation speed on the blade angle and the resulting voltage in the electric system, the change in the power factor and efficiency of a wind power plant depending on the wind speed was carried out.CONCLUSION. The developed wind turbine has a power of 2.6 W at a wind speed of 4 m / s. This invention is recommended for the purpose of teaching methods of design and construction of similar installations. For the developed wind turbine, it is possible to optimize the work using the method of numerical three-dimensional thermogasdynamic modeling, to evaluate the nature of the flow at off-design operating modes, which speeds up the process of creating the final installation and improves its efficiency parameters.